INVENTORY MANAGEMENT AND PERFORMANCE OF BRAZILIAN FIRMS (2010-2016) - Cardoso, Guilherme Freitas; Quirós, Dannie Delanoy Carr; Souza, Guilherme Santos; CARVALHO, LUCIANO FERREIRA; Ribeiro, Kárem Cristina de Sousa (Anais do Congresso Brasileiro de Custos - ABC, 2017)
The inventory management faces a trade-off which affects firms in the relationship between maintaining high inventories and decreasing the probability of stock-outs or keeping inventory levels lower and applying the excess cash to other investments. Thus, this paper will investigate the relationship that exists between inventory management and performance between-financial Brazilian firms listed in the BM&FBovespa from 2010 to 2016. Inventory is not a relevant factor in the revenues of all the firms of the initial sample. The sample is refined through a simple linear regression to only comprise firms with a significant relationship between inventory and revenue. The results indicate that the model which considers Tobin’s Q measurement of performance shows that there is no relationship between inventory and performance. However, a robustness check was done using the ROA to measure the performance and in this scenario, there is a statistically inverted U-shaped relation between the profitability, the net trade cycle and its square. This means that H1 and H2 would be confirmed and from these results the study found an optimal level of 244.87 days. These findings have relevant practical guidelines to the Brazilian firms and researchers in the analysis of the performance related to the net trade cycle, which it can be suggested that the Brazilian shareholders are not concerned about internal factors, as the inventory management, but if the firm is being managed profitable.